2023
DOI: 10.1007/s10571-023-01344-6
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Stem Cells as a Potential Treatment Method for Selected Neurodegenerative Diseases: Review

Abstract: Stem cells have been the subject of research for years due to their enormous therapeutic potential. Most neurological diseases such as multiple sclerosis (MS), amyotrophic lateral sclerosis (ALS), Alzheimer's disease (AD), Parkinson's disease (PD), and Huntington's disease (HD) are incurable or very difficult to treat. Therefore new therapies are sought in which autologous stem cells are used. They are often the patient's only hope for recovery or slowing down the progress of the disease symptoms. The most imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 180 publications
1
7
0
Order By: Relevance
“…Altogether, several clinical trials have been performed addressing the safety of MSC transplantation in patients with NDD. Overall, the results of these studies support the safety and feasibility of the transplantation of both autologous and allogeneic MSCs [103]. Published reports have shown that no tumors were formed because of the transplant, and no deaths occurred because of the therapeutic intervention.…”
Section: Cell Therapy In Alzheimer's Disease: Key Findings From Clini...supporting
confidence: 66%
See 1 more Smart Citation
“…Altogether, several clinical trials have been performed addressing the safety of MSC transplantation in patients with NDD. Overall, the results of these studies support the safety and feasibility of the transplantation of both autologous and allogeneic MSCs [103]. Published reports have shown that no tumors were formed because of the transplant, and no deaths occurred because of the therapeutic intervention.…”
Section: Cell Therapy In Alzheimer's Disease: Key Findings From Clini...supporting
confidence: 66%
“…Although several clinical trials have been conducted or are ongoing to evaluate the efficacy along with the safety profile of MSC therapy in NDD, few published results are available [103]. In the NCT01297218 and NCT01696591 studies [97], the administration of allogeneic hUCB-MSCs to the hippocampus and precuneus by stereotactic injection in patients with AD had no dose-limiting toxicity during 2 years of follow-up.…”
Section: Cell Therapy In Alzheimer's Disease: Key Findings From Clini...mentioning
confidence: 99%
“…Such therapies could involve drugs (e.g., monoclonal antibodies) inhibiting the actions of proteins inducing MSCs homing to tumor sites and leading to the attenuation of cancer progression. Furthermore, MSCs are considered in treatments of broad spectrum of conditions, including cancer [ 65 ], diabetes [ 66 ], myocardial infarction [ 67 ], bone-related dysfunctions [ 68 ] or neurodegeneration [ 69 ]. Therefore, delineation of the mechanisms that regulate MSCs’ migration is crucial for further development and improvement of therapies utilizing engineered MSCs that are currently evaluated in clinical trials [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…NSCs have been explored as a potential therapeutic avenue for replacing neurons lost to CNS disorders [ 283 ]. Despite their promise, the clinical application of NSC therapy faces significant hurdles, including immune rejection in the absence of substantial immunosuppression, low rates of cell engraftment, teratoma formation risks, and the invasiveness of intracerebral transplantation.…”
Section: Applications Of Evs As Nanotheranostic Targets In Cnsmentioning
confidence: 99%